Creep Properties of Axially Compressed Fly Ash Concrete under Sulfate Corrosion. (12th September 2022) - Cao, Jian; Han, Ziyang; Du, Zhifeng
Abstract : Creep, sulfate erosion resistance, fly ash content of concrete, and sustained compression load are important factors that will affect the long-term performance of concrete. It is of great interest to combine these effects together to make a comprehensive investigation of fly ash concrete. However, the concrete creep under both sustained compression load and sulfate attack conditions has rarely been reported. To obtain the creep characteristics of fly ash concrete in a sulfate environment, this paper first finishes the creep experiments of fly ash concrete under sustained compression load and sulfate attack. The test factors include the load stress level, the concentration of sulfate solution, and the content of fly ash. Based on the creep mechanism of fly ash concrete under sulfate erosion, the relationship between time-dependent section area variation and creep was carried out. After comparing different creep models, the creep calculation model of fly ash concrete under sulfate erosion was built via the B4 model combined with the cross-sectional area of the damaged layer and undamaged layer of concrete. Finally, comparing the calculated values with the test results, the calculated results were in good agreement with the test data, which is of practical significance to the practical engineering application and the improvement of structural reliability.